Festival Semarapura Tahun 2025 sebagai Event Budaya dan Ekonomi Kreatif di Kabupaten Klungkung - Ni Kadek Sri Mirayani; I Gusti Ngurah Oka Widjaya; Ni Putu Lilik Widyayanthi; Isvari Ayu Pitanatri; Ni Putu Tiya Paristha (Yayasan Literasi Sains Indonesia, 2025)
The Semarapura Festival is an annual cultural event organized by the Klungkung Regency Government through the Department of Tourism. The 7th Semarapura Festival in 2025 is held with the aim of strengthening local cultural identity while developing the community’s creative economy sector. This study aims to analyze the implementation of the 2025 Semarapura Festival as a cultural and creative economy event. The research method used is descriptive qualitative with a case study approach through observation, interviews, and documentation. The results show that the Semarapura Festival plays an important role as a medium for cultural preservation through traditional art performances and activities based on local wisdom, as well as serving as a platform for creative economic development for MSME actors in the culinary and craft sectors. In addition, the festival also applies environmentally friendly innovations and digital promotion strategies through social media to expand audience reach. However, challenges such as parking areas, lack of shaded spaces, and waste management still need attention to optimize the festival in the future. Overall, Semarapura Festival in 2025 succeeds in becoming a model cultural event that integrates tradition preservation, creative economy empowerment, and environmental sustainability.